Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1007/s40273-014-0150-1
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness Analyses in Multiple Sclerosis: A Review of Modelling Approaches

Abstract: The growing number of disease-modifying treatments (DMTs) for patients with multiple sclerosis (MS) and the high acquisition costs of these DMTs are likely to increase the demand for information on their cost effectiveness. To improve the comparability and applicability of the findings from future cost-effectiveness analyses, it would be useful to have a clear understanding of the methodological challenges of modelling the cost effectiveness of DMTs in MS and the different approaches taken by such studies to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
48
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(50 citation statements)
references
References 42 publications
2
48
0
Order By: Relevance
“…Our review of the most recent economic evaluations conducted in the EU setting on first-generation DMDs confirms the widespread concern raised in previous wider reviews [6][7][8][9]. First, most studies were based on long-term modeling and they all had to rely on weak sources to populate them [8].…”
Section: Policy Implicationssupporting
confidence: 78%
See 2 more Smart Citations
“…Our review of the most recent economic evaluations conducted in the EU setting on first-generation DMDs confirms the widespread concern raised in previous wider reviews [6][7][8][9]. First, most studies were based on long-term modeling and they all had to rely on weak sources to populate them [8].…”
Section: Policy Implicationssupporting
confidence: 78%
“…All these CoIs used the 'human capital approach' to assess indirect cost, a controversial method that is likely to lead to overestimates and implies a state of full employment in the long run [17], which is hardly the case in the EU countries in this period of unprecedented economic crisis. Last but not least, all the studies gave the clear impression of being part of the manufacturers' marketing strategies, trying to highlight high social costs for MS to demonstrate the value of their product [7][8][9].…”
Section: Policy Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the basis of title and abstract, 966 records were excluded and the remaining 57 records were included for full-text screening. A further 48 articles were excluded at the full-text stage, leaving nine systematic reviews, [245][246][247][248][249][250][251][252][253] of which eight were economic evaluation studies [245][246][247][248][249][250][251][252] and one was a systematic review of studies that used a generic tool to measure HRQoL in people with multiple sclerosis. 253 …”
Section: Resultsmentioning
confidence: 99%
“…We identified several related systematic reviews of cost-effectiveness evaluations in RRMS in the overview of systematic reviews. [245][246][247][248][249][250][251][252][253] Therefore, we performed searches for primary cost-effectiveness studies from the earliest search date found in these selected reviews (i.e. 2012) to April 2016.…”
Section: Introductionmentioning
confidence: 99%